Gender differences in mathematics : a discourse analysis - MacLeod, Catriona (School of Education, 2024)
The majority of perspectives from which the study of gender and mathematics has been approached have failed to move beyond the· individual/society divide. The contradictory nature of subjectivity and the operation and interpenetration of power and knowledge in the production of that subjectivity has n~t been taken into account. This thesis is based on the theoretical framework of post-structuralistn. The literature concerning gender differences in mathematics is criticized from this framework. In particular, the work of Walkerdine and her colleagues, which highlights the processes within the classroom which allow girls to succeed in mathematics but never actually be successful, is of interest. The methodology of choice in this study is that of discourse analysis which makes clear both the positionings available to the participants as well as the power relations formed. The sample was drawn from a topachieving Std 8 Higher Grade class in an affluent Model C school. This sample represents a theoretically salient sample as the literature points to the 'differences' being most pronounced in the upper levels of mathematics education. The analysis clearly highlights the double-bind within which girls find themselves in the mathematics classroom. The apparent equality of opportunity and non-sexism is counteracted by the positioning of girls as hard-working but without natural flair in mathematics. The characteristics that make it possible to achieve in mathematics are ascribed to males. The resistance to t~is powerful 'disciplinary technology' is the invoking of the feminist discourse, which was done by some of the females in the study.. It appears that there are very real barriers to girls' participation and achievement in mathematics. These barriers lie within the power relations and discourses/knowledges surrounding gender issues and mathematics education.